MODELING OF STRUCTURE UNDER THE MOUNTAIN PAPANDAYAN BASED ON MAGNETIC PROPERTIES OF ROCK - PATRICIA (NIM : 10213087), NAOMI
Mount Papandayan is located on Cisurupan Area, Garut District, West Java, about 70 km southeast of Bandung. This mountain is classified as an active volcano in Indonesia which is located on 2665 meter above sea level. This volcano has some craters; they are Kawah Mas, Kawah Baru, Kawah Nangklak, and Kawah Manuk. Based on those conditions, Mount Papandayan has the potential of geothermal which could be renewable energy source. The potential could be identified by magnetic method as its subsurface magnetic variation. In this research, magnetic method survey was run on 12 km2 area on Mount Papandayan area. The collected data of magnetic variation were processed by forward modelling method and inversion method. The results showed some anomalies of magnetic field about -120 nT to 580 nT. This anomali showed the geothermal potential in Mound Papandayan. The anomaly models were detected on depth of 30 meter to 500 meter subsurface. The anomaly models had two susceptibility ranges. The first anomaly model had susceptibiliy value about 0.0162 to 0.0516 which could be indicated as the basalt rock. The second one had susceptibiliy value about 0.237 which could be indicated as ilmenit rock.